Simplified Poultry Keeping - Alexandra (‏Independently published, 1864)
12.5 linear feet (12 boxes) : | Materials consist of over 400 catalogs, almanacs, pamphlets, magazines, and newspapers from the 19th and 20th centuries. Topics include poultry and other livestock, animal treatments, and farming equipment, manuals, and techniques. Arranged alphabetically by company name | Box 1 includes publications produced by the following companies : | Box 2 includes publications produced by the...
Selon les droits indiques dans Internet Archive
Keywords: internet archive; livre; histoire; Géographie; bibliotheque numerique